Patient and Family Perpetrated Cyber-Incivility and Cyber-Aggression Within Healthcare: A Cross-Sectional Descriptive Study - Cara Spencer; Kelsey Loehr; Abby Byrd (SAGE Publishing, 2023)
Introduction Verbal violence may manifest in written form as cyber incivility within patient portal communications. As a form of digital technology, patient portal messages create a physical and emotional distance leading the sender to be disinhibited and disassociated from the recipient nurse. Written patient portal messages may contain uncivil language deemed verbally violent when the content escalates beyond professional standards. When these messages are encountered as part of patient care, they may lead to nurses' psychological distress. Although cyber-incivility has been studied within social media and business, little is known about cyber-incivility within healthcare. Objectives The purpose of the study was to define cyber-incivility as it manifests within healthcare compared to business, determine sender demographics, and quantify the impact on nurses. Methods A cross-sectional descriptive study was conducted to analyze portal communications. Nurses forwarded aggressive messages to leadership and quantified their level of distress after receiving the message. Sender demographics were tracked, and content was analyzed using Braun and Clarke's Thematic Analysis. Results Of the 31 included messages, senders were of varying ages, genders, and marital statuses. Messages rarely related to medications and rarely contained expletives. The most distressing messages were ad hominem, demanding, accusatory, or contained threats. These messages illustrated how healthcare cyber-incivility manifested and deviated from appropriate professional standards to become a form of verbal workplace violence. Message content also identified antecedents; related to unmet expectations, patient accountability, or difficulty navigating healthcare. Conclusions Written incivil/uncivil/aggressive patient portal messages contained personal attacks and professionally degrading content, which were distressing to nurses. A healthcare-specific framework was created and provided context to understand the difficult and aggressive messages nurses received while providing digital patient care. Awareness of cyber-incivility within healthcare allows for better support of nurses who are exposed to this form of workplace violence and is foundational to future intervention development.